Lean Manufacturing and Overall Equipment Efficiency (OEE) in Paper Manufacturing and Paper Products Industry - Fam, S.F.; Ismail, N.; Yanto, H.; Prastyo, D.D.; Lau, B.P. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The purpose of this article is to study the relationship between lean manufacturing methods and overall equipment efficiency (OEE) in paper manufacturing and paper product industry using the one-year data (Jan 2015 - Dec 2015) of five lean manufacturing tools namely single-minute exchange of die (SMED), standardized work (SW), takt time, value stream mapping (VSM) and Kaizen. The current data, which is based on the five lean tools, is compared with the past data which is collected prior to the usage of such tools. Both current and past data are analyzed using IBM SPSS version 22 and the results show that the lean methods are able to reduce waste and increase the OEE. This empirical study gives valuable information to the paper manufacturers and paper product industry in Malaysia on the utilization of lean machines for improving quality and productivity management.